Age‐specific incidence and treatment patterns of head and neck cancer in the Netherlands—A cohort study. (12th October 2017) - Halmos, G.B.; Bras, L.; Siesling, S.; van der Laan, B.F.A.M.; Langendijk, J.A.; van Dijk, B.A.C.
Abstract : Objectives: To explore the incidence and treatment pattern of head and neck cancer in different age groups. Design: Cohort study. Setting: Netherlands Cancer Registry. Participants: All new primary head and neck cancer cases diagnosed between 2010 and 2014 were included and categorised into different age groups. Main outcome measures: Tumour site, stage, treatment modality, location of diagnosis and treatment. Results: The study population was composed of 11 558 tumours. Oral cancer was the most common primary site (31%), followed by laryngeal (25%) and oropharyngeal cancer (22%). Ninety‐six per cent of the entire study population was diagnosed and/or treated in a certified head and neck oncology centre which was lower in the 80+ population (92%). Multimodality treatment was less frequently applied with increasing age (eg oral cavity: 17% in 80+ vs 34% in 60−; P < .001). The percentage of patients not receiving tumour‐directed treatment increased with age (eg oropharyngeal cancer: 25% in 80+ vs 6% in 80−; P < .001). Conclusions: This study confirms that less multimodal and tumour‐directed treatment is applied with the increasing age of head and neck cancer patients.